Prawodawstwo Konferencji Episkopatu Polski i Prymasów w zakresie sakramentów wtajemniczenia chrześcijańskiego - Janczewski, Zbigniew (Prawo Kanoniczne, 1997)
Three sacraments of the Christians initiation - baptism, confirmation and Eucharist are very difficult for the life of the Church. This article shows the legislation of the Conference Episcopate of Poland and polisch primates in the scope of those sacraments. The Conference Episcopate is legislator in the paricular Church from Council Vatican II, the primates of our country from the year 1945 on the base extraordinary licenses from the Holy See.